Cтановлення української мови - Іванько, І. К. (ХНУРЕ, 2022)
This report assumes that such a Ukrainian language, where and when it appeared. In the assumption that the Ukrainian language is repeated as a language with numerous variations, it is also about deepening its development with an in-depth study of the times up to the present day.